FAM96A Protects Mice From Dextran Sulfate Sodium (DSS)-Induced Colitis by Preventing Microbial Dysbiosis - Yin, Ang; Luo, Yang; Chen, Wei; He, Minwei; Deng, Jin Hai; Zhao, Ning; Cao, Lulu; Wang, Lu (Frontiers in Cellular and Infection Microbiology, 2019)
FAM96A is an evolutionarily conserved intracellular protein, that is involved in maturing the Fe/S proteins iron regulatory protein 1 (IRP1) and the mitochondrial related apoptosis of gastrointestinal stromal tumor cells. In this article, we used a mouse model of chemically induced colitis in order to investigate the physiological role of FAM96A in intestinal homeostasis and inflammation. At baseline, colons from Fam96a-/- mouse exhibit microbial dysbiosis, dysregulated epithelial turnover, expansion of goblet cell numbers, disorder of tight junctions with functional deficits in intestinal permeability. After cohousing, these differences between wild-type and Fam96a-/- colons were abrogated, suggesting that FAM96A affects colonic epithelial cells in a microbiota-dependent way. Fam96a deficiency in mice results in increased susceptibility to dextran sodium sulphate (DSS)-induced colitis. Importantly, the colitogenic activity of Fam96a-/- intestinal microbiota is transferable to wild-type littermate mice via fecal microbial transplantation (FMT) experiment, leading to exacerbation of DSS-induced colitis. Taken together, our data indicate that FAM96A maintains colonic homeostasis and protects against DSS-induced colitis via preventing gut microbial dysbiosis. This study uses gene knockout animals to extend the cognition of the Fam96a gene in vivo for the first time and provides new evidence for host-microbiota interactions.